2022
DOI: 10.7189/jogh.12.05031
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival benefit of male and multimorbid COVID-19 patients with 5-day remdesivir treatment

Abstract: Background Treatment of the coronavirus disease (COVID-19) is still challenging due to the lack of evidence-based treatment protocols and continuously changing epidemiological situations and vaccinations. Remdesivir (RDV) is among the few antiviral medications with confirmed efficacy for specific patient groups. However, real-world data on long-term outcomes for a short treatment course are scarce. Methods This retrospective observational cohort study included real-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
7
3
2
Order By: Relevance
“…However, 30-days mortality (3.8%) was lower than that in the ACTT-1 (11%), WHO's Solidarity (15%) and DisCoVeRy (8%) trials (9,12,21). In most (22)(23)(24) but not all (25) observational studies 30-days mortality and/or disease progression rates in patients treated with 5day remdesivir were higher than in our study being around 12-13%. In a recently published Greek study, a 10% mortality rate was reported in three Greek hospitals (4% in 14 days), with a 9-day mean interval between admission and recovery [26].…”
Section: Discussioncontrasting
confidence: 76%
“…However, 30-days mortality (3.8%) was lower than that in the ACTT-1 (11%), WHO's Solidarity (15%) and DisCoVeRy (8%) trials (9,12,21). In most (22)(23)(24) but not all (25) observational studies 30-days mortality and/or disease progression rates in patients treated with 5day remdesivir were higher than in our study being around 12-13%. In a recently published Greek study, a 10% mortality rate was reported in three Greek hospitals (4% in 14 days), with a 9-day mean interval between admission and recovery [26].…”
Section: Discussioncontrasting
confidence: 76%
“…Patients with ILD were started on steroid therapy, and a subsequent followup study assessed the reduction of previous symptoms and described the regression of CT abnormalities; highlighting that CT lesions did not progress to fibrosis in patients treated with steroids (Myall et al 2021). In our patients steroids were used during the hospital stay in high proportion as standard of care treatment, non-treated patients were mainly from the group of referrals who had their infection at home (Polivka et al 2022). This might have contributed to the lower number of pulmonary changes on LDCT.…”
Section: Discussionmentioning
confidence: 98%
“…Based on our national protocol, indication for oxygen administration was arterial partial pressure of oxygen (PaO 2 ) <60 mm Hg or peripheral oxygen saturation (SpO 2 ) <90% at room air [ 16 ]. The initial strategy was a low-flow system up to 2 L/min via nasal cannulae and was increased over 6 to 15 L/min with reservoir facemask.…”
Section: Methodsmentioning
confidence: 99%
“…The initial strategy was a low-flow system up to 2 L/min via nasal cannulae and was increased over 6 to 15 L/min with reservoir facemask. For those requiring low-flow oxygen, a 5-day-long remdesivir regimen and dexamethasone 8–16 mg oral/8–16 iv were administered [ 16 ]. Patients with a persistent need for hig- flow oxygen (>60 L/min) or showing rapid progression over hours, hemodynamic instability or multiorgan failure needed mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%